Integration of Ethnoscience in Science Learning Media: Learning about Temperature and Heat through the Traditional Salt Making Process - Lalu Muhammad Rispan Sugi Saputra (International Journal of Science Education and Science, 2026)
This study explores the effectiveness of video-based learning media in teaching the concepts of temperature and heat through the traditional salt production process. Conducted at SMP Islam Assunnah Bagik Nyaka in East Lombok Regency, the study involved 25 seventh-grade students and 4 teachers. The method used was community service, consisting of three stages: preparation, implementation, and evaluation. In the preparation stage, the researcher observed the science curriculum to select relevant topics, namely temperature and heat, and developed a video depicting the salt production process. During the implementation stage, the video was used as an instructional tool to facilitate interactive discussions between teachers and students about the scientific principles involved in salt production. Evaluation was carried out by collecting feedback from students and teachers through questionnaires assessing the appeal, relevance, and effectiveness of the media in enhancing understanding. The results showed a high satisfaction level (86%) among students, who found the video helpful in understanding the concepts. This study emphasizes the importance of culturally relevant teaching methods in increasing student engagement and understanding of scientific concepts, while also promoting appreciation for local traditions.